Altered gut microbiomes are associated with the symptomatic status of unruptured intracranial aneurysms - Sun, Kaijian; Cao, Ying; Chen, Yiting; Peng, Qing; Xie, Yugu; Luo, Yunhao; Tian, Hao; Li, Xin; Zeng, Meiqin; Zhang, Xin; Li, Xifeng; Su, Shixing; et al. (Frontiers in Neuroscience, 2022)
Background Gut microbiome has recently been recognized as an important environmental factor affecting the occurrence and development of unruptured intracranial aneurysms (UIA). This study aimed to investigate the relationship between gut microbiome and symptomatic UIA, which is a predictor of instability and a high propensity to rupture. Methods A total of 132 patients including 86 asymptomatic UIA and 46 symptomatic UIA were recruited in the study. The composition of gut bacterial communities was determined by 16S ribosomal RNA gene sequencing. In addition, Phylogenetic Investigation of Communities by Reconstruction of Unobserved States (PICRUSt) was used to predict the functional composition of the gut microbiome. Results There is no difference in the fecal microbial alpha diversity between symptomatic and asymptomatic UIA, but gut microbiome composition changed significantly. At the order level, the relative abundance of Clostridiales was significantly enriched in the symptomatic compared with asymptomatic UIA (p = 0.043). In addition, similar alterations were observed at the family levels of Ruminococcaceae. The Linear discriminant analysis (LEfSe) revealed Fournierella, Ruthenibacterium and Anaerotruncus as a discriminative feature in the symptomatic group. Notably, functional differences in gut microbiome of patients with symptomatic UIA included decreased propionate metabolism pathway and enrichment of peptidoglycan biosynthesis pathways. Conclusion The present study comprehensively characterizes gut microbiome in a large cohort of different risk statuses of UIA patients and demonstrates the potential biological function of gut microbiome involved in the development of UIA. It may provide additional benefit in guiding UIA management and improving patient outcomes.